Interlimb coordination during the stance phase of gait in subjects with stroke - Andreia S. P. Sousa (2013)
Objective: To analyse the relation between contralesional and ipsilesional limbs in subjects with stroke during step-to-step transition of walking.Design: Observational, transversal, analytical study with a convenience sample.Setting: Patients from a physical medicine and rehabilitation clinic in Portugal (Braga).Participants: Sixteen subjects with post-stroke hemiparesis with the ability to walk independently and twenty-two healthy controls.Interventions: Not applicable.Main outcome measures: Bilateral lower limbs electromyographic activity (EMG) of soleus (SOL), gastrocnemius medialis (GM), tibialis anterior (TA), biceps femoris (BF), rectus femoris (RF) and vastus medialis (VM) muscles and ground reaction force were analysed during double support and terminal stance phases of gait.Results: The propulsive impulse of the contralesional trailing limb was negatively correlated to the braking impulse of the LEAD limb during double support (r=-0.639, p=0.010). A moderate functional relation was observed between thigh muscles (r=-0.529, p=0.035), and a strong and moderate dysfunctional relation was found between the plantar flexors of the ipsilesional limb and the vastus medialis of the contralesional limb, respectively (SOL-VM, r=-0.800, p<0.001; GM-VM, r=-0.655, p=0.002). Also, a functional moderate negative correlation was found between the SOL and RF muscles of the ipsilesional limb during terminal stance and between the SOL (r=-0.506, p=0.046) and VM (r=-0.518, p=0.040) muscles of the contralesional limb during loading response, respectively. The trailing limb relative impulse contribution of the contralesional limb was lower than the contribution of the ipsilesional limb of subjects with stroke (p=0.02) and lower than the relative impulse contribution of the healthy limb (p=0.008) during double-support.Conclusions: The findings obtained suggest that the lower performance of the contralesional limb in forward propulsion during gait is not only related to contralateral supraspinal damage but also to a dysfunctional influence of the ipsilesional limb.